Influence Of Satisfaction, Commitment, And Trust Customer To Customer Loyalty Gojek Users In Bandar Lampung - Sanakri, Kiky (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
In this modern era, people have various activities and to fulfill the needs of these activities, people need transfers as fork equipment or auxiliary equipment in carrying out their activities. One of the online transfer services currently available among the public is Gojek Indonesia, which is an online transfer service application that can be used on smartphones. To offer compliance to its customers, currently the services offered by Gojek range from a service system for accompanying passengers using motorized transportation, a food delivery service system, to a one day grocery shopping service system. The aim of this research is to identify the effects of Happiness, Commitment and Confidence in Compliance on Gojek consumers in Bos Lampung. The research used is quantitative research and the sampling method used in this research is probability sampling. The number of examples obtained was 81 respondents, namely Gojek clients in Bos Lampung. Based on the research results, it shows that satisfaction and trust elasticities have an impact on Gojek client compliance in Bos Lampung, while for elastic commitments it has no effect on Gojek client compliance in Bos Lampung. In this research the elastic effects of Satisfaction, Commitment and Confidence affect 78% of Gojek client compliance in Bos Lampung. Conversely, more than 22% is influenced by other aspects not monitored in this research.